(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify (the effectiveness of the learning anchors model in the levels of mathematical understanding of middle school students in mathematics) To verify the aim of the current research, the two researchers adopted the semi-experimental approach, and the research sample consisted of (40) male and female students from the first intermediate grade students, the second semester of the academic year (2023-2022 AD), Al-Yaqoubi Mixed Secondary School of the Directorate of Education of Baghdad Al-Karkh II was chosen. Intentional choice, and random selection of the people, Division (A) was chosen to be the experimental group that was studied according to the learning anchors model, with (20) male and female students, consisting of (11) male and (9) female students, and Division (B) to be the control group that was studied according to The usual method, with (20) male and female students, which consisted of (11) male and (9) female students, and the two groups were rewarded in the following variables (intelligence, chronological age, previous information in mathematics, and previous achievement in mathematics( The research tool was prepared, which is: Testing levels of mathematical comprehension according to eight levels (primitive knowledge, shape making, shape possession, property observation, generalization, observational understanding, composition (construction), and invention) consisting of (160) Objective paragraphs (multiple choice) and essays with (20) mathematical concepts. Each concept has eight paragraphs according to levels of mathematical understanding. It has been divided into two parts, each part includes (10) mathematical concepts. And using the alpha-Cronbach equation, the value of the stability coefficient was 0.78. After the completion of the experiment, the test was applied to the two research groups. The spss_20 statistical program was used to process the data obtained, and the results showed that there was a statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group and the scores of the students of the control group in the mathematical comprehension levels test, in favor of the experimental group according to the method of teaching, and there was no difference according to the gender variable and the interaction between teaching method and gender. In the light of the results of the research, the researcher recommends working to direct the attention of officials in charge of education in the Ministries of Higher Education, Scientific Research and Education, to the need to pay attention to the model of learning anchors in teacher preparation programs, as well as training courses for mathematics teachers during service. It is proposed to study the impact of the learning anchors model on other variables such as the acquisition of concepts, flexible understanding, and deep understanding